There Are Plenty of Atheists in Foxholes - in Sweden - Granqvist, Pehr (Archive for the psychology of religion, 2014)
We evaluated the veracity of a famous aphorism that is often cited in the scientific study of religion: “There are no atheists in foxholes.” To provide a critical evaluation, the sample was drawn from one of the world’s most secular spots, Sweden. We explored the prevalence of various religious beliefs/non-beliefs and prayer in a sample of parents (n = 57) living with a major threat: having a child with a life-threatening heart condition. For comparison purposes, the prevalence of such beliefs and prayer were explored also in a sample (n = 72) of parents with healthy children. Results showed that a majority of parents endorsed atheist or agnostic beliefs, whereas only a minority endorsed religious beliefs. Roughly half of the sample engaged in prayer. The group of parents with sick children was statistically indistinguishable from the comparison group parents on all variables. Also, between-group differences were generally negligible in terms of effect size; thus, the null results were not due to statistical power problems. We conclude that there may be plenty of atheists in some foxholes.